1985
DOI: 10.1128/iai.50.1.97-101.1985
|View full text |Cite
|
Sign up to set email alerts
|

Factors governing adherence of Candida species to plastic surfaces

Abstract: The ability of Candida albicans and Candida spp. to adhere to inert polymeric surfaces may allow these organisms direct ingress into the human host. Biophysical characterization of this adherence shows that the forces responsible for such adherence are attractive London-van der Waals forces (or hydrophobic forces) and electrostatic forces. The hydrophobic affinity of yeasts was determined by (i) a water-hydrocarbon two-phase assay and by (ii) measurement of the contact angle (theta) of a liquid droplet on a mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
181
1
5

Year Published

1994
1994
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 315 publications
(193 citation statements)
references
References 28 publications
6
181
1
5
Order By: Relevance
“…to adhere to and colonize acrylic surfaces. Virulence factors of Candida spp., such as cell-surface hydrophobicity [27] and ability to form biofilm [10], increase its adherence to acrylic surfaces. Other investigations have also demonstrated that Candida spp.…”
Section: Discussionmentioning
confidence: 99%
“…to adhere to and colonize acrylic surfaces. Virulence factors of Candida spp., such as cell-surface hydrophobicity [27] and ability to form biofilm [10], increase its adherence to acrylic surfaces. Other investigations have also demonstrated that Candida spp.…”
Section: Discussionmentioning
confidence: 99%
“…The cell surface hydrophobicity (CSH) of C. albicans cells was determined exactly as described previously [14]. In the present study, n-hexadecane was used as non-polar solvent.…”
Section: Cell Surface Hydrophobicitymentioning
confidence: 99%
“…However, it is also apparent that the adherence process is not explainable by one single specific event and that several different specific interactions may be occurring [4] or that 'non-specific' forces or events may be contributing to the adherence process. For example, it has long been recognized that hydophobicity contributes to adhesion or adherence of C. albicans in vitro [5] and perhaps in vivo [6]. Although recognized earlier in work on Candida adherence [5], the role of electrostatic forces in the process of adherence of this fungus to substrates has never been investigated systematically.…”
Section: Introductionmentioning
confidence: 99%
“…For example, it has long been recognized that hydophobicity contributes to adhesion or adherence of C. albicans in vitro [5] and perhaps in vivo [6]. Although recognized earlier in work on Candida adherence [5], the role of electrostatic forces in the process of adherence of this fungus to substrates has never been investigated systematically.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation